Evaluating how child allowances and daycare subsidies affect fertility - Joshua R. Goldstein; Christos Koulovatianos; Jian Li; Carsten Schröder (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
We compare the cost effectiveness of two pronatalist policies: (a) child allowances; and (b) daycare subsidies. We pay special attention to estimating how intended fertility (fertility before children are born) responds to these policies. We use two evaluation tools: (i) a dynamic model on fertility, labor supply, outsourced childcare time, parental time, asset accumulation and consumption; and (ii) randomized vignette-survey policy experiments. We implement both tools in the United States and Germany, finding consistent evidence that daycare subsidies are more cost effective. Nevertheless, the required public expenditure to increase fertility to the replacement level might be viewed as prohibitively high.
urn:nbn:de:hebis:30:3-430067
Keywords: J13; J18; J38; D91; C83; D10; C38; 330; childcare; fertility; labor supply; vignette survey method; public policy